Integrated weed management approaches for sustainable weed suppression and yield optimization in aerobic rice - Govindan, S K; Natarajan, S; Ramalingam, S; Swaminathan, M; Gomasa, S; Kasirajan, S; Kaliaperumal, R; Sellaperumal, P (Plant Science Today, 2025)
Aerobic rice, grown in well-drained non-puddled non-saturated soils, is a promising water saving approach that can reduce water consumption compared to traditional methods, but weed infestation remains a major constraint that significantly limits crop growth and yield. A two-year field study was conducted to evaluate effective combinations of physical and chemical methods along with various agronomic practices to analyse the impact of various weed management methods for aerobic rice cultivation. The study was conducted using a randomized block design, with three replications in ten treatment combinations. Among the different weed control strategies, the weed-free treatment recorded the lowest weed density (2.48 weeds/m² at maximum tillering and 3.39 weeds/m² at panicle initiation stage), highest weed control efficiency (94.7 % at maximum tillering and 93.2 % at panicle initiation stage), lowest weed index and highest grain yield (4977 kg/ha). This was followed by Pre-Emergence (PE) application of pendimethalin (0.75 kg/ha) at 5 DAS (Days After Sowing) followed by mechanical weeding at 30 DAS resulted in reduced weed density (5.37 weeds/m² at tillering and 9.12 weeds/m² at panicle initiation), improved weed control efficiency (73.76 % and 48.52 %) and a grain yield of 4833 kg/ha, this treatment also recorded the highest Benefit-Cost (B:C) ratio (2.23), establishing it as the most economically viable and profitable approach for weed management in aerobic rice cultivation. It was comparable to the chemical control using PE pendimethalin followed by Early Post-Emergence (EPoE) application of bispyribac sodium (25 g/ha) at 25 DAS, which recorded a B:C ratio of 2.00.